Secure communication in the digital age: a new paradigm with graph-based encryption algorithms - Ali, Nasir; Sadiqa, Ayesha; Shahzad, Muhammad Amir; Imran Qureshi, Muhammad; Siddiqui, Hafiz Muhammad Afzal; Abdallah, Suhad Ali Osman; Abd El-Gawaad, Nashaat S. (Frontiers in Computer Science, 2024)
In the contemporary technological landscape, ensuring confidentiality is a paramount concern addressed through various skillsets. Cryptography stands out as a scientific methodology for safeguarding communication against unauthorized access. Within the realm of cryptography, numerous encryption algorithms have been developed to enhance data security. Recognizing the imperative for nonstandard encryption algorithms to counter traditional attacks, this paper puts forth novel encryption techniques. These methods leverage special corona graphs, star graphs, and complete bipartite graphs, incorporating certain algebraic properties to bolster the secure transmission of messages. The introduction of these proposed encryption schemes aims to elevate the level of security in confidential communication, some of the applications of these schemes are given in the later section.